A propósito de la reciente aprobación del “Proyecto de Ley que reestablece la autonomía universitaria” - González Fretel, César Daniel (2022)
Approximately eight years ago, Law N° 30220 or University Law was enacted, which sought to promote the continuous improvement of the educational quality of university institutions and established the National Superintendence of University Higher Education as the supervisory body. However, in May 2022, the Plenary of the Congress approved the so-called “Bill that reestablishes university autonomy”. In this sense, the interview seeks to analyze and evaluate the meaning and consequences of such project in the Peruvian educational environment.